Метод статистических испытаний эффективности алгоритмов оценки ионосферных параметров в методе НР - Мазманишвили, Александр Сергеевич; Пуляев, Валерий Александрович (НТУ "ХПИ", 2003)
Numerical experimental results of with multiparameter statistical model are given with the purpose of revealing influence of processing methods on accuracy and reliability of ratings ionospheric data
Keywords: околоземная плазма; ионосфера; метод некогерентного рассеяния; зондирующие сигналы; автокорреляционные функции; плазма